Kyrgyz Republic : Fourth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Waiver of Nonobservance of Performance Criterion. (IMF Staff Country Reports; Country Report ;, 2004)
The Kyrgyz Republic has made good progress under the Poverty Reduction Growth Facility (PRGF)-supported economic program. Executive Directors commended the sound policies, low inflation, and poverty reduction. They appreciated the strong fiscal discipline, and monetary and exchange rate policies. They emphasized the need to accelerate structural reforms, strengthen the financial system, and restructure the electricity sector. They stressed the need to reduce corruption and improve governance so as to promote investment and growth. They congratulated authorities for the successful implementation of the second PRGF, and granted a waiver.